Admission serum magnesium levels associated with short- and long-term clinical outcomes in COVID-19 patients. (3rd October 2022) - Segev, A; Sagir, A; Matezky, S; Segev, A; Atar, S; Shechter, M
Abstract: Introduction: In the face of the global pandemic coronavirus disease 2019 (COVID-19) has created, readily available prognostic markers may be of great use. Purpose: To evaluate the association between serum magnesium levels (sMg) on admission and clinical outcomes in hospitalized COVID-19 patients. Methods: We retrospectively analyzed all consecutive patients admitted to our medical center with a primary de novo diagnosis of COVID-19.Demographic, clinical and laboratory data were extracted from the electronic medical record. Clinical outcomes were compared between five groups of patients according to the quintiles of sMg on hospital admission. Results: From 2, 433 consecutive COVID-19 patients during the years 2020–2021, we included 1, 522 patients with sMg on admission (1–3 day of hospitalization) (58% male, 69±17 years old). Patients were followed for a mean of 10±7 months. A low sMg level (1st quintile) was associated with higher rates of diabetes and steroid use, whereas a high sMg level (5th quintile) was associated with dyslipidemia, chronic kidney disease, andhigher levels of inflammatory markers (Table 1). Both low and high sMg levels were associated with lower oxygen saturation during hospitalization. All-cause in-hospital and long-term mortality was higher in patients with both low and high sMg levels, compared with mid-range sMg levels (2nd, 3rd and 4thquintiles; 19% and 30% vs. 9.5%, 10.7% and 17.8% and 35% and 45.3% vs. 23%, 26.8% and 27.3% respectively; p<0.001 for all) (Figure 1). Conclusions: Both low and high sMg levels were associated with worse short- and long-term clinical outcomes and all-cause mortality in a large cohort of hospitalized COVID-19 patients. Thus, admission sMg levels may play a prognostic role in risk stratificationof COVID-19 patients. Funding Acknowledgement: Type of funding sources: None.